1961
DOI: 10.1021/j100819a024
|View full text |Cite
|
Sign up to set email alerts
|

THE FREE ENERGY, ENTROPY AND ENTHALPY OF TRANSFER OF SODIUM AND POTASSIUM CHLORIDE FROM METHANOL TO WATER AND FROM ETHYLENE GLYCOL TO WATER1,2

Abstract: dine reaction and a standard entropy change of £°= -8.0 cal./mole. Thus the present results by the n.m.r. method are quite consistent with the earlier work of Vinogradov and Linnell3 who obtained for this reaction a AH of -3.8 ± 0.2 kcal. from calorimetric measurements and an equilibrium constant of 22 ±3 at 30°from infrared measurements in CCU solutions.The significance of the variation of calculated " with temperature is uncertain. Temperature dependent n.m.r. effects, however, frequently indicate associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

1967
1967
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…For calculation of the values for activity coefficient of NaCl in pure methanol from eq 8, it was assumed that the short-range contribution to the values of activity coefficient of NaCl in pure methanol is the same as that of pure water as solvent. Perhaps the disagreement of the values for activity coefficients of NaCl in pure methanol from this study (eq 8) with the corresponding experimental values of Gladden and Fanning is the result of this assumption. However, Kamps used an extension of Pitzer’s equation for the excess Gibbs energy of aqueous electrolyte solutions, parameters for which were fitted to the experimental data for the osmotic coefficient which in turn were calculated from vapor pressure measurements (0.04 < m < 0.22).…”
Section: Calculations and Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…For calculation of the values for activity coefficient of NaCl in pure methanol from eq 8, it was assumed that the short-range contribution to the values of activity coefficient of NaCl in pure methanol is the same as that of pure water as solvent. Perhaps the disagreement of the values for activity coefficients of NaCl in pure methanol from this study (eq 8) with the corresponding experimental values of Gladden and Fanning is the result of this assumption. However, Kamps used an extension of Pitzer’s equation for the excess Gibbs energy of aqueous electrolyte solutions, parameters for which were fitted to the experimental data for the osmotic coefficient which in turn were calculated from vapor pressure measurements (0.04 < m < 0.22).…”
Section: Calculations and Resultscontrasting
confidence: 67%
“…The calculated activity coefficients of sodium chloride in (0.5 w/w) methanol/water mixed solvent systems at all concentrations (0 ≤ m ≤ m sat ) are given in Figure c. The stoichiometric activity coefficients of NaCl in methanol/water mixed solvents at 298.15 K are compared with the available literature data in Figure . The values for activity coefficients of NaCl in pure methanol at 298.15 K from this study (eq 8) disagree with the corresponding values reported by Kamps, and both sets of data disagree with the activity coefficient data of Gladden and Fanning at higher concentrations (Figure d).…”
Section: Calculations and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from Figure , the activity coefficients calculated from the data by Yan et al are nicely represented (average relative deviation = 2.4%), whereas the ones calculated from the data by Gladden and Fanning 115 are not consistent with the data reported by Barthel et al (The data of Gladden and Fanning, also at other temperatures, were therefore discarded in the present work.)
2 Mean ionic activity coefficient of NaCl in CH 3 OH at 298.15 K: (□) Gladden and Fanning; (·) Yan et al; () prediction, this work.
…”
Section: Modelingmentioning
confidence: 74%
“…The mean ionic activity coefficient of sodium chloride in methanol (on the molality scale) is where Gladden and Fanning as well as Yan et al reported some emf data for methanolic solutions containing sodium chloride at T = 298.15 K. These data have been reevaluated; i.e., the standard electrode potentials were recalculated by means of the usual extrapolation procedureusing Pitzer's modified Debye−Hückel term as used hereand the mean ionic activity coefficients of sodium chloride were redetermined by using those (slightly different numbers for the) standard electrode potentials. As can be seen from Figure , the activity coefficients calculated from the data by Yan et al are nicely represented (average relative deviation = 2.4%), whereas the ones calculated from the data by Gladden and Fanning 115 are not consistent with the data reported by Barthel et al (The data of Gladden and Fanning, also at other temperatures, were therefore discarded in the present work.)…”
Section: Modelingmentioning
confidence: 99%